Re-discover student engagement from the perspective of definition and influencing factors - Wang, Qian (Frontiers in Psychology, 2025)
In recent, the topic of student engagement has received a great deal of academic attention. However, there are numerous definitions of student engagement. Will this lead to inaccuracies and ambiguities in future definitions of student engagement? Therefore, it is important to have a common understanding of student engagement. In this paper, I present three definitions of student engagement that have the potential to be widely accepted. Additionally, in order to study student engagement in more depth, it is crucial to focus factors that influence student engagement. In this paper, 30 articles from three databases, Google Scholar, Taylor & Francis Online, and SAGE, were screened for data analysis based on the inclusion criteria. Three influences were extracted from the included articles, namely student self-control, teacher empathy, and learning environment, which were analyzed as possible indirect influences. An interesting finding is that the learning environment may act as a direct influence. Meanwhile, in order to improve student engagement, this paper draws on Schneider and Ingram’s categorization of policy tools, e.g., authority, incentive, and capacity tools, then formulates a causal model of the influences on student engagement, as well as provides a number of interventions, and finally offers some insights.